Dictionary of British Arms Medieval Ordinary : Volume Four - Flower, Sarah; Woodcock, Thomas (Dictionary of British Arms, 2014)
This is the fourth of a four-volume collection of British heraldic arms, arranged alphabetically according to their designs and covering the period before 1530. Listed within this volume are entries from Fetterlock to Wreath, completing the collection. This book will help readers to identify the arms that were widely displayed in the Middle Ages and which can now be found not only on tombs, monuments and seals, but also on textiles, manuscripts, metalwork, glass, wall paintings, and other medieval artefacts. The index allows even those without any specialist knowledge of the subject to discover the blazons of arms recorded for particular surnames in the medieval period. Produced specifically to enable readers to identify individual coats of arms, it is an invaluable reference for historians, antiquaries, archaeologists, genealogists and those dealing in and collecting medieval objects.